The Profile of an Intercultural Higher Education Student in Mexico at One Hundred Years from the Cosmic Race - González Ortiz, Felipe (2022)
Basic indigenous education and intercultural higher education are concepts that refer to two meta-narratives that respond to two historical contexts that delineate the relationship between the State and the indigenous children and youth in the field of education. If, at the beginning of the 20th century, cultural integration was proclaimed through basic education, the 21th century intercultural education stands as an emerging response to globalized multiculturalism. The questions in this essay focus on the differences in this complex relationship and open routes for linking a permanent process of cultural integration of the indigenous to the modern society called national.